Prion-Like Domains in Phagobiota - Tetz, George; Tetz, Victor (Frontiers in Microbiology, 2017)
Prions are molecules characterized by self-propagation, which can undergo a conformational switch leading to the creation of new prions. Prion proteins have originally been associated with the development of mammalian pathologies; however, recently they have been shown to contribute to the environmental adaptation in a variety of prokaryotic and eukaryotic organisms. Bacteriophages are widespread and represent the important regulators of microbiota homeostasis and have been shown to be diverse across various bacterial families. Here, we examined whether bacteriophages contain prion-like proteins and whether these prion-like protein domains are involved in the regulation of homeostasis. We used a computational algorithm, prion-like amino acid composition (PLAAC), to detect prion-like domains in 370,617 publicly available bacteriophage protein sequences, which resulted in the identification of 5040 putative prions. We analyzed a set of these prion-like proteins, and observed regularities in their distribution across different phage families, associated with their interactions with the bacterial host cells. We found that prion-like domains could be found across all phages of various groups of bacteria and archeae. The results obtained in this study indicate that bacteriophage prion-like proteins are predominantly involved in the interactions between bacteriophages and bacterial cell, such as those associated with the attachment and penetration of bacteriophage in the cell, and the release of the phage progeny. These data allow the identification of phage prion-like proteins as novel regulators of the interactions between bacteriophages and bacterial cells.